2022
DOI: 10.1177/17456916211071087
|View full text |Cite
|
Sign up to set email alerts
|

Why Warmth Matters More Than Competence: A New Evolutionary Approach

Abstract: Multiple lines of evidence suggest that there are two major dimensions of social perception, often called warmth and competence, and that warmth is prioritized over competence in multiple types of social decision-making. Existing explanations for this prioritization argue that warmth is more consequential for an observer’s welfare than is competence. We present a new explanation for the prioritization of warmth based on humans’ evolutionary history of cooperative partner choice. We argue that the prioritizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 159 publications
0
9
0
Order By: Relevance
“…This finding is interesting in light of recent work suggesting that adults place greater value on the willingness to provide benefits than on factors like competence or a partners' access to resources (Dhaliwal et al., 2022; Eisenbruch & Roney, 2017; Raihani & Barclay, 2016). This tendency is thought to reflect a partner‐choice strategy tailored to the conditions that were characteristic of the ecologies in which human social cognition evolved, where generosity varied more than competence between partners (Eisenbruch & Krasnow, 2022). However, in most studies providing the basis for this theorizing, generosity was directly relevant to the tasks participants had to recruit partners for—typically some type of economic game—while other qualities such as knowledgeability, intelligence, or physical prowess were not.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is interesting in light of recent work suggesting that adults place greater value on the willingness to provide benefits than on factors like competence or a partners' access to resources (Dhaliwal et al., 2022; Eisenbruch & Roney, 2017; Raihani & Barclay, 2016). This tendency is thought to reflect a partner‐choice strategy tailored to the conditions that were characteristic of the ecologies in which human social cognition evolved, where generosity varied more than competence between partners (Eisenbruch & Krasnow, 2022). However, in most studies providing the basis for this theorizing, generosity was directly relevant to the tasks participants had to recruit partners for—typically some type of economic game—while other qualities such as knowledgeability, intelligence, or physical prowess were not.…”
Section: Discussionmentioning
confidence: 99%
“…One future direction in the study of character complexity could examine how perceptions of character vary across history and culture for each of the “big two”—operationalized in various research programs as trustworthiness/warmth/communion versus dominance/competence/agency (Abele et al, 2021; Fiske, 2018; Oosterhof & Todorov, 2008). Recent research has found that attributes related to warmth or trustworthiness are more insensitive to niche diversity than attributes that signal dominance or competence (Eisenbruch & Krasnow, 2022). This work was focused on explaining why warmth matters more than competence in person perception, but it also has implications for asymmetric perceptions of warmth and competence complexity as societies grow larger and more complex.…”
Section: Discussionmentioning
confidence: 99%
“…One future direction in the study of character complexity could examine how perceptions of character vary across history and culture for each of the "big two"-operationalized in various research programs as trustworthiness/warmth/communion vs. dominance/competence/agency (Abele et al, 2021;Fiske, 2018;Oosterhof & Todorov, 2008). Recent research has found that attributes related to warmth or trustworthiness are more insensitive to niche diversity than attributes which signal dominance or competence (Eisenbruch & Krasnow, 2022). This work was focused on explaining why warmth matters more than competence in person perception, but it also has implications for asymmetric perceptions of warmth and competence complexity as societies grow larger and more complex.…”
Section: Do Our Findings Apply To All Forms Of Social Cognition?mentioning
confidence: 99%